1997
DOI: 10.4319/lo.1997.42.3.0473
|View full text |Cite
|
Sign up to set email alerts
|

Diatom growth and productivity in an oligo-trophic midocean gyre: A 3-yr record from the Sargasso Sea near Bermuda

Abstract: We measured the rate of biogenic silica production in the upper 160 m at the Bermuda Atlantic Time-series Study (BATS) site in the western Sargasso Sea on 12 cruises between August 1991 and May 1994 using a 30Si tracer method. Previously initiated time series of particulate silica concentrations and the gravitational flux of siliceous particles were extended to produce an October 1988-December 1994 time series for biogenic silica concentrations and August 1991-December 1994 time series for lithogenic silica co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
149
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 129 publications
(163 citation statements)
references
References 37 publications
13
149
1
Order By: Relevance
“…Depth integrated (0 -140 m) bSiO 2 production rates averaged 1.03 ± 0.96 (n = 17) and 2.28 ± 2.06 (n = 9) mmol Si m -2 d -1 for the West and East Transects, respectively, a substantial increase over previous Sargasso Sea measurements (Brzezinski and Kosman, 1996;Brzezinski and Nelson, 1995;Nelson and Brzezinski, 1997). For example, Nelson and Brzezinski (1997) in a three year study (1992)(1993)(1994) at BATS. During our cruise, integrated bSiO 2 stocks were also enhanced by a factor of 2.5 in the East relative to the West Transects coincident with a temporal increase in vertically integrated bSiO 2 (2.5 mmol m -2 on YD68 to ~4.5 mmol m -2 on YD70) and NO 3 -concentrations (from ~18 mmol m -2 to ~55 mmol m -2 ) (Krause et al, 2008;Lomas et al, 2008a).…”
Section: Bsio 2 Exportmentioning
confidence: 77%
See 3 more Smart Citations
“…Depth integrated (0 -140 m) bSiO 2 production rates averaged 1.03 ± 0.96 (n = 17) and 2.28 ± 2.06 (n = 9) mmol Si m -2 d -1 for the West and East Transects, respectively, a substantial increase over previous Sargasso Sea measurements (Brzezinski and Kosman, 1996;Brzezinski and Nelson, 1995;Nelson and Brzezinski, 1997). For example, Nelson and Brzezinski (1997) in a three year study (1992)(1993)(1994) at BATS. During our cruise, integrated bSiO 2 stocks were also enhanced by a factor of 2.5 in the East relative to the West Transects coincident with a temporal increase in vertically integrated bSiO 2 (2.5 mmol m -2 on YD68 to ~4.5 mmol m -2 on YD70) and NO 3 -concentrations (from ~18 mmol m -2 to ~55 mmol m -2 ) (Krause et al, 2008;Lomas et al, 2008a).…”
Section: Bsio 2 Exportmentioning
confidence: 77%
“…Krause et al (2008) measured bSiO 2 silica production rates during this study using the 32 Si tracer and incubation method described by Brzezinski and Phillips (1997) and Brzezinski et al (2001). Depth integrated (0 -140 m) bSiO 2 production rates averaged 1.03 ± 0.96 (n = 17) and 2.28 ± 2.06 (n = 9) mmol Si m -2 d -1 for the West and East Transects, respectively, a substantial increase over previous Sargasso Sea measurements (Brzezinski and Kosman, 1996;Brzezinski and Nelson, 1995;Nelson and Brzezinski, 1997). For example, Nelson and Brzezinski (1997) in a three year study (1992)(1993)(1994) at BATS.…”
Section: Bsio 2 Exportmentioning
confidence: 88%
See 2 more Smart Citations
“…These and other systemic biological responses to nutrient variations are well described (see Michaels and Knap, 1996;Steinberg et al, 2001 and citations within). Patterns of primary production (Menzel and Ryther, 1960;Lohrenz et al, 1992;Michaels and Knap, 1996;Steinberg et al, 2001) and the temporal variability of specific phytoplankton groups have been studied extensively at BATS with a variety of approaches, including radiotracers (Brzezinski and Nelson, 1995;Nelson and Brzezinski, 1997), photosynthetic pigment proxies (Bidigare et al, 1990;Goericke, 1998;Steinberg et al, 2001;Lomas and Bates, 2004), flow cytometric measurements of phytoplankton abundance (Olson et al, 1990;Li et al, 1992;DuRand et al, 2001) and growth (Li et al, 1992;Worden and Binder, 2003a, b;Cuvelier et al, 2010). Most notably, a recent study at BATS showed a 450% increase in chlorophyll a (Chl a) data between 1996 and 2007 (Lomas et al, 2010).…”
Section: Introductionmentioning
confidence: 99%